Clinical study of symptoms recovering from Covid-19 for different segments of Iraqi society - Alali, Urjwan; Farhan, Noor Hadi; Majeed, Ali Hameed (Technium BioChemMed, 2025)
An outbreak of pneumonia of unknown origin was reported in Wuhan, Hubei Province, China, in December 2019. It was identified as SARS-CoV-2, which was previously called 2019-nCov. They are grouped into four genera: alpha, beta, gamma, and delta coronaviruses. SARS-CoV-2 symptoms vary from mild to severe. Fever, cough, and shortness of breath are the most common symptoms. This epidemic has spread throughout various countries of the world, and the number of infected people has increased very rapidly. Among these countries is Iraq, which recorded the first Corona virus in the Najaf Governorate, on February 24, 2020 and thereafter, as the number of infections began to rise steadily, specifically in the third month of 2021. In this study, questionnaire forms were used, and the cases showed those infected with the Corona virus from several governorates in Iraq (Wasit, Diyala, Karbala). Then the health problems that continued to occur after recovery were discussed. The infected cases were analyzed statistically, which were related to some of the symptoms that appeared among males and females.